2022
DOI: 10.1142/s1793042123500306
|View full text |Cite
|
Sign up to set email alerts
|

Infinite families of class groups of quadratic fields with 3-rank at least one: quantitative bounds

Abstract: We improve an effective lower bound on the number of imaginary quadratic fields whose absolute discriminants are less than or equal to [Formula: see text] and whose ideal class groups have 3-rank at least one, which is [Formula: see text]. We also obtain a better bound on the number of imaginary quadratic fields with 3-rank at least two, which is [Formula: see text]; the best-known lower bound so far is [Formula: see text]. For finding these effective lower bounds, we use the Scholz criteria and the parametric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Yu also demonstrated that for sufficiently large X, there are >> X 1 2 −ǫ such fields with discriminant −D, where D ≤ X. In another work [50], Yu established that the number of real quadratic fields with discriminant ≤ X and class number divisible by n is >> X 1 n −ǫ for any ǫ > 0 and any odd n. Siyun Lee, Yoonjin Lee, and Jinjoo Yoo [35] have made advancements in providing effective lower bounds on the number of imaginary quadratic fields with absolute discriminants less than or equal to X and ideal class groups having a 3-rank of at least one, which is >> X 17 18 . Additionally, they determined that the number of imaginary quadratic fields with a 3-rank of at least two is >> X…”
Section: Quantitative Results On Divisibility Of Class Numbers Of Qua...mentioning
confidence: 99%
“…Yu also demonstrated that for sufficiently large X, there are >> X 1 2 −ǫ such fields with discriminant −D, where D ≤ X. In another work [50], Yu established that the number of real quadratic fields with discriminant ≤ X and class number divisible by n is >> X 1 n −ǫ for any ǫ > 0 and any odd n. Siyun Lee, Yoonjin Lee, and Jinjoo Yoo [35] have made advancements in providing effective lower bounds on the number of imaginary quadratic fields with absolute discriminants less than or equal to X and ideal class groups having a 3-rank of at least one, which is >> X 17 18 . Additionally, they determined that the number of imaginary quadratic fields with a 3-rank of at least two is >> X…”
Section: Quantitative Results On Divisibility Of Class Numbers Of Qua...mentioning
confidence: 99%